Hegemoni Kekuasaan Dalam Pandangan Agama Hindu Dalam Karya Sastra Puisi Modern “Korupsi “ Karangan Nyoman Tusthi Eddy - Ida Bagus Gede Paramita (Pramana: Jurnal Hasil Penelitian, 2021)
The purpose of this study is to examine the hegemony of power contained in modern Balinese literature by Nyoman Tusthi Eddy. The aspects studied in this article are the relationship between ideology, power and literary works, especially in corruption poetry and the views of Hindu religious teachings on corrupt behavior. The method used in this research is qualitative method. Primary data was obtained from the text of “Korupsi” poems, while secondary data was obtained from books and online publications that support the research discussion. The collected data is then selected to assist the analysis and the last step is drawing conclusions. The results of this study are the discovery of the author's ideology in criticizing the behavior of corruptors, and when the readership of this poem reads it will be influenced by the author's ideology to be anti-corruption behavior. In addition, this article also examines corruption from the point of view of Hinduism and what the punishment is